Spectrum of vaginal foreign body in children: A report of two cases - Pankaj Halder; Kartik Chandra Mandal; Lopamudra Mishra; Bidyut Debnath (Wolters Kluwer Medknow Publications, 2017)
An extraordinary type of foreign body (FB) may be found in the female external genitalia, especially in children. Intravaginal FB, retained for long duration, can produce diagnostic dilemma. Vaginal bleeding as the result of a leech bite is extremely rare although reported. We report two cases of vaginal FB (intravaginal Scotch-Brite in a 5-year-old girl and leech in the vagina in a 7-year-old girl).